STUDENTS’ BELIEFS ABOUT SOCIAL MEDIA IN EFL CLASSROOM: A REVIEW OF LITERATURE - Anita Dewi Ekawati (University of Kuningan, 2022)
This article reviews research on student beliefs about the use of social media in English as a Foreign Language (EFL) classrooms. This study involves a discussion of how social media impacts students' language learning from previous studies. This study uses a systematic literature review (SLR) in reviewing articles. In determining the article, it is carried out in three stages, namely peer-reviewed articles, re-examined articles, and analyzing the selected articles. The literature review summarizes research on student beliefs from 2017 to 2021. A total of seven articles are referenced in this study. The conclusion drawn from the seven literatures is that students' beliefs about the use of social media in EFL classrooms are positively affected. Social media helps students to improve their English skills. The use of social media can be a reference for teach media that EFL teachers can present in learning activities to attract students' attention and achieve goals in language learning.